HUBUNGAN USIA PENGENALAN MP-ASI TERHADAP KEJADIAN STUNTING PADA BALITA KELURAHAN RANGAS KECAMATAN BANGGAE KABUPATEN MAJENE - Rahmaniah; Fauziah; Kasma, Andi Sri Rahayu; Mayangsari, Riska; Kasma, Andi Yulia (Universitas Sulawesi Barat, 2023)
Stunting is one of the nutritional problems experienced by several countries in the world, especially developing countries including Indonesia. The prevalence of stunting in Majene Regency reaches 35.7%. The purpose of this study was to determine the relationship between the age at which complementary foods were introduced and the incidence of stunting. The population in this study were toddlers aged 24-59 months. The sample in this study was obtained using a saturated sample technique, namely the entire population was sampled. To analyze the test data used the chi-square test. The results of the statistical test showed a p value (0.038) <0.05, which means that there is a relationship between the age of introduction of breastfeeding and the incidence of stunting in toddlers. Toddlers with an earlier introduction of weaning food have a risk of 2.595 times experiencing stunting compared to toddlers whose introduction of weaning food is on time Keywords: stunting; weaning food; toddlers.